Upaya Meningkatan Pengetahuan Siswa/Siswi SMK Farmasi As-Shifa Ciparay Kelas XII Terkait Mencuci Tangan dengan 7 Langkah yang Baik dan Benar dengan Memakai Sabun: Pengabdian - Ahmad Zaelani; Indah Rifdailah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community outreach programme is part of the lecturers' obligations. The aim of this programme is to help the community realise the importance of washing their hands before and after doing something. The activity carried out at the As-Shifa Ciparay Pharmacy Vocational School was a health education session with the theme